FOOD AND KITCHEN AS RECLAIMING OF WOMANHOOD IN DIANA ABU-JABER'S MEMOIRS - Anasya fazira Stia putri; Hasnul Insani Djohar (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2026)
Food plays a central role in Arab-American women’s writing because it bridges personal memory, cultural identity, and gendered experience. While previous studies have examined food as nostalgia or cultural preservation, fewer have explored how culinary practices and kitchen spaces function as feminist sites of agency and identity negotiation within the diasporic context. This Paper focuses on Diana Abu-Jaber’s memoirs The Language of Baklava (2006) and Life Without a Recipe (2016) using the perspective of Food Studies, Arab-American Feminism and Diaspora Theory. The analysis aims to explore how food function as a narrative tool for Arab-American women to express identity, memory, and resistance within patriarchal and cross-cultural contexts. With Gaul’s (2024) concept of food cultural and emotional symbol as main theory, this paper argues that Abu-Jaber transform the kitchen from domestic space into a site of empowerment and negotiation. This study employs qualitative content analysis to examine recurring food narratives, memories, and kitchen spaces in both memoirs, using close reading supported by theoretical categorization. The Result found that food in Abu-Jaber’s memoir is not merely a cultural representation, but a feminist language that bridges Arab and American experiences. Through culinary memory, recipe, and everyday cooking, Abu-Jaber redefines female agency and articulates a hybrid Arab-American identity. The study conclude that Abu-Jaber’s memoirs reflect a distinct form Arab-American feminism where food and the kitchen serve as mediums of self-expression, cultural preservation and resistance.